Influence of deposit formation on corrosion at the high-temperature superheater of eucalyptus-fired boiler. (2nd January 2023) - Wei, Yuwei; Kuang, Yunkun; Li, Guohua; Li, Weichao; Chen, Weichong; Han, Jianxiong; Zhang, Kun; Zhu, Lin; Li, Yongjun
ABSTRACT: Eucalyptus biomass-fired boilers generally experience severe problems with deposit formation and are expected to suffer from severe superheater corrosion at high temperatures due to the large alkali and chlorine content in eucalyptus biomass. The unique deposition layer structure and corrosion mechanism of eucalyptus-fired boilers are discussed in this paper. It was found that a unique sandwich like cell-membrane structure on the heating surface was formed in eucalyptus biomass-fired boilers. Chlorine acts as a catalyst, circulates the reaction and causes serious corrosion. The oxides at the junction of the corrosion layer and the matrix mainly penetrate along the grain boundary of the matrix, forming a unique network structure. There is obvious internal oxidation and mass transfer along the grain boundary in the matrix of 12Cr2MoWVTiB steel pipe, and no obvious internal oxidation in SA213T91 steel pipe due to its fine and uniform grains.